Lexicostatistics of Javanese and Sasak Languages: Comparative Historical Linguistic Studies - Mahriyuni; Isda Pramuniati; Rizky Ainun Maftuhah (Mimbar Ilmu, 2023)
A language is related to other languages because these languages are similar to one another. The kinship between Javanese and Sasak languages can be seen in lexical and phonemic correspondences. This study aims to analyze the kinship relationship based on numerical calculations between the Javanese and Sasak languages and the lexicostatistical order of the two languages. This research uses qualitative and quantitative methods. Data were obtained using the literature study method, corresponding to Morris Swades' 200 basic vocabulary using direct note-taking techniques. Data analysis used the lexicostatistics method. The result of the research is that after lexicostatistical calculations have been carried out, the percentage of kinship between Javanese and Sasak languages is 23.8%. Based on the error analysis, it is known that Javanese and Sasak were a single language around 1553-1317 years ago. The Javanese and Sasak languages are estimated to have started to separate from Proto around 469 – 705 AD (calculated by 2022).